1978
DOI: 10.2165/00003495-197816040-00001
|View full text |Cite
|
Sign up to set email alerts
|

Mianserin

Abstract: Mianserin is a tetracyclic compound advocated for the treatment of depressive illness and depression associated with anxiety. It combines antidepressant activity with a sedative effect and has an EEG and clinical activity profile similar to that of amitriptyline. It has an overall efficacy comparable with amitriptyline and imipramine in depressive illness, but at dosages which have achieved a similar overall clinical improvement, mianserin causes significantly fewer anticholinergic side effects than amitriptyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(9 citation statements)
references
References 210 publications
1
8
0
Order By: Relevance
“…The dibenzo [b,e]azepine ring is an important pharmacophore in drug discovery and many of its derivatives exhibit a broad spectrum of biological activities (Van der Burg et al, 1970;Brogden et al, 1978;Nickolson & Wieringa, 1981;Berger et al, 1989;De Boer et al, 1996;Roeder et al, 1998;André s et al, 2002;Wikströ m et al, 2002). Consequently, a significant number of synthetic methods have been developed for the synthesis of new derivatives of this heterocyclic system (Moriconi & Maniscalco, 1972;Sasakura & Sugasawa, 1981;Stappers et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The dibenzo [b,e]azepine ring is an important pharmacophore in drug discovery and many of its derivatives exhibit a broad spectrum of biological activities (Van der Burg et al, 1970;Brogden et al, 1978;Nickolson & Wieringa, 1981;Berger et al, 1989;De Boer et al, 1996;Roeder et al, 1998;André s et al, 2002;Wikströ m et al, 2002). Consequently, a significant number of synthetic methods have been developed for the synthesis of new derivatives of this heterocyclic system (Moriconi & Maniscalco, 1972;Sasakura & Sugasawa, 1981;Stappers et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…They are supramolecules with a hydrophobic interior, which may include hydrophobic parts of the drug molecule and hydrophilic shells, consisting of primary and secondary hydroxyl groups that can interact with water molecules [13,14]. In pharmacological tests of the mianserin antidepressant effect [15], higher potency is found for the optical enantiomer (S)-(+)-mianserin. However, we chose the racemate for testing, since commercially available mianserin hydrochloride is a racemic mixture.…”
Section: Introductionmentioning
confidence: 99%
“…It blocks presynaptic receptors (α 2 -adrenoreceptors) responsible for the binding of serotonin and the mechanism of mianserin action allows for prolonged action of both hormones (noradrenaline and serotonin) improving the mood of a person suffering from depression. [4][5][6][7] In pharmacological tests of antidepressant activity 4 a higher potency is present for the (S)-(+)-mianserin optical enantiomer. A pharmacokinetic study with mianserin hydrochloride indicated that the maximum anticipated oral availability was calculated to be in the range of 34-49%.…”
Section: Introductionmentioning
confidence: 99%